Um estudo sobre o método de investigação da psique na obra de C. G. Jung - Penna, Eloisa Marques Damasco (2003)
The question of method in the works of C.G. Jung was not an area neglected by Jungians or by Jung himself, but the systematization of such provoked IiUle interest in the Jungian community. Some reasons for this gap in Jungian literatura have been identified in this study, which aims to systematize the method for investigating the psyche in the works of C. G. Jung. This systematization, has been undertaken in light of the existing concept of the paradigm that stresses the inter-connection of ontological, epistemological and methodological perspectivas in the composition of a paradigm. Based on a chronological approach to the construction of Jung's method, an evolutionary line can be drawn for defining the methodological concepts and assumptions, from the Word association test to the concept of synchronicity and formulation of symbolic amplification to approach psychic phenomena. The conception of unconscious and conscious psychic totality that integrates the internal and external worlds and includes personal and collective aspects within a archetypal symbolic dimension, constituias the ontological base for the Jungian paradigm. The epistemological perspectiva concentrates on the possibility of accessing the collective and personal unconscious through its manifestations - symbols - which are the epistemological bridge between unconscious, conscious and culture. Knowledge and self-knowledge are inseparable. Knowledge is produced through the constant forrnation and transformation of consciousness in search for integration and elaboration of symbols - the individuation process - the individual's continuous movement toward differentiation and complexity. The distinctive mark of Jung's method for investigating the psyche is his archetypal symbolic perspectiva in understanding psychic phenomena. This perspectiva approaches phenomena based on the parameters of causality, purpose and synchronicity and understanding is achieved by archetypal symbolic thought that flows by means of comparisons and analogias that enrich and amplify the unconscious meanings contained in the symbol amplification. Until the middle of the twentieth century, the ideas of C. G. Jung received severa criticism trem the scientific community, since they were considered to be toa general and not scientific enough for the scientific standards of the time. Today, one can observe a growing acceptance of analytical psychology in the existing scientific panorama. Certain approximations between the Jungian paradigm and the characteristics of post-modern science are becoming evident